Why Islamic Institutions Function Best in The West - (:unkn) unknown (RESEARCH CENTER ISLAMIC ECONOMICS-IKAM, 2020)
The gist of this paper is that the once superb Islamic institutions of the past nowadays function best in the West but stagnate in their very birthplace. I argue that this is because pre-conditions referred to in this paper are not available in the latter. Ever since the 1960s, too much hope has been placed on Islamic finance with hardly any attention been paid to these pre-conditions. Unless this emphasis is radically altered, Islamic finance, no matter how well designed, would have only a marginal impact on the sustained economic growth of Islamic countries.
Keywords: Waqfs; Universities; Sustained economic growth; Islamic banks; Parliamentary democracy; Freedom of thought and its expression